ANALISIS PERTIMBANGAN HAKIM TERKAIT TINDAK PIDANA PENCEMARAN NAMA BAIK TERHADAP SEORANG JURNALIS - Lyra, Bernadeta; Soehartono, Soehartono (Sebelas Maret University, 2024)
This article analyzes the judge's judgment in the Journalist defamation case in Cassation Decision Number 5940 K/PID. SUS/2022 regarding the criminal charge of a journalist named Muhammad Asrul who published news on online media owned by the media company where he worked which was associated with the provisions of Law Number 40 of 1999 concerning the Press. This type of research is normative legal research that is prescriptive with secondary data types including primary and secondary legal materials. The technique of collecting legal materials is carried out by literature study, then the analytical technique used is the deductive method. This study produces the researcher's view on the judge's consideration in imposing prison sentences on journalists for their journalistic work not paying attention to Law Number 40 of 1999 on the Press as a lex specialist which should be the main guideline. Terminating press cases using the Information and Electronic Transactions deviates from the principles of press freedom.